INTEGRATION OF ADSORPTION PROCESS AND MEMBRANE ELECTROCHEMICAL REACTOR TO REMOVE TRIHALOMETHANES IN DRINKING WATER TREATMENT - Tazkiaturrizki Tazkiaturrizki; Djoko M Hartono; Sandyanto Adityosulindro; Ni Putu Sri Wahyuningsih (Universitas Trisakti, 2025)
Trihalomethanes (THMs) are disinfection by-products formed from the reaction of disinfectants with natural organic matter (NOM). Aims: This study aimed to analyze the presence of NOM as precursors and THMs removal using a integration of granular activated carbon (GAC) and electrochemical membrane reactor (MER) in drinking water treatment (DWT). Methodology and results: Analysis of GAC performance in reducing NOM through variations in carbon dosage and reaction time. MER is an advanced treatment to reduce THMs in drinking water treatment with parameters of current density and reaction time. The DWT raw water contained NOM: DOC concentration of 5.18 ± 1.99 mg/L and SUVA of 2.04 ± 1.02 L/mg m. Conventional DWT remove 4-60% of NOM. The addition of GAC increases NOM removal up to 68%. MER can remove THM with 40 - 80% for chloroform and bromodichloromethane, while for chlorodibromomethane and bromoform, the removal is 10-50%. Conclusion, significance and impact study: The integration of GAC-MER increases NOM removal up to 90%, and the integration of MER-GAC reduce THMs up to 40-62%. The optimum condition of MER for NOM and THMs removal is at a current density of 20 mA cm-2 and a reaction time of 1 hour. This study is expected to be useful for DWT to control the formation of DBPs that are harmful to human health. The application of MER can reduce DBP as well as other pollutants because MER treatment is a combined treatment of membrane filters and electro-oxidation, and the addition of GAC increases the pollutant removal.